FRI0475 Systemic Sclerosis (SSC) Related Calcinosis: Patients Provide what Specialists Want to Learn – Development of a Calcinosis Patient Reported Outcome Measure (PROM). (9th June 2015) - Christensen, A.M.; Khalique, S.; Cenac, S.; Fligelstone, K.; Jaeger, V.; Mawdsley, A.; Kaufman, R.; Frech, T.; Gordon, J.K.; Steen, V.; Aubin, A.; Baron, M.; et al.
Abstract : Background: Calcinosis is a disabling, rarely discussed manifestation of SSc for which the natural history and management is poorly understood. This investigation is the 1st phase of a multi-tiered project to understand calcinosis from patients' perspectives creating the groundwork for a SSc-calcinosis PROM. Methods: Five focus groups and individual interviews in the US and UK were recorded and transcribed verbatim. Pathophysiologic and life impact were elicited with: 1. Since developing calcinosis how has your life changed over time? 2. How has calcinosis changed over time? A final probe was a request for questions that a clinician could ask to understand if calcinosis was better, worse or same. Transcripts were analysed by hand (highest method) by an iterative inductive process (content drives coding) by at least 5 independent analysts including at least one patient research partner. Concepts were triangulated until a comprehensive set of concepts emerged. Occurrence was quantified per participant. Results: Twenty-three patients (29/31 female, 27/31 white, with mean disease duration 18.1 years) were consented and interviewed. Responses spanned broadly to include concepts of self-management strategies and recurrent hypotheses relating calcinosis development to trauma, Raynaud's and cold exposure (tables 1 & 2 ). Cold exposure and Raynaud's were a perceived association to calcinosis severity - "when they are cold mine always open back up". A majority of patients engage in strategies to extrude calcinosis with either pressure +/- soaking or at home surgical techniques. "I actually have homemade surgical tools to get these out." The following anchors were consistently suggested for physicians to assess calcinosis severity: pain level, size, frequency, number and functional impairment. A 2-step question was suggested to help differentiate ulcer, infection and calcinosis symptoms: 1st regarding predomiant wound character and then target the related calcinosis. Conclusions: These results provide the groundwork for and conclude the 1st steps (item collection) in PROM development. As suggested by patients, a composite of scales anchored in pain, size, frequency, number and related impairment may reasonably serve as an interim instrument for SSc calcinosis. Next steps are validating content with a large subject base and questionniare development with subsequent validation. Very importantly, patients' observations and self-management behavior provide opportunities to learn from and to preemptively educate physicians and patients. Patients are eager for self-management guidance. An essential deliverable of this work will be a patient-physician education guide on calcinosis management. Acknowledgements: In memory of Anne Mawdsley, founder: Raynaud's & Scleroderma Association UK – tireless engine for education and advocacy raising >£10 million for SSc research. Disclosure of Interest: A. Christensen: None declared, S. Khalique: None declared, S. Cenac: None declared, K. Fligelstone: None declared, V. Jaeger: None declared, A. Mawdsley: None declared, R. Kaufman: None declared, T. Frech: None declared, J. Gordon: None declared, V. Steen: None declared, A. Aubin: None declared, M. Baron: None declared, E. Busman: None declared, L. A. Saketkoo Grant/research support from: ACR/EULAR Exchange Awardee